Biogenic Amines in Food: Presence and Control Measures - Elias, Miguel (2019)
Biogenic amines (BA) or biologically active amines are low molecular weight nitrogenous compounds formed from amino acids by decarboxylation, or by amination and transamination of aldehydes and ketones. Due to their precursor amino acids structure and origin, BA are classified as either aliphatic diamines, aromatic biogenic amines or natural polyamines. Biogenic amines in foods have relevance from both safety and quality standpoints. They may be found in a wide range of foods containing proteins or free amino acids including meat, dairy and fish products, vegetables, fruits, wine, beer, nuts and chocolate. The biogenic amines most commonly found in foods are cadaverine, putrescine, tyramine, histamine, tryptamine, β-phenylethylamine, agmatine, spermine and spermidine, the two latter being endogenous amines. Additionally, octopamine and dopamine have been reported in meat and fish products. In non-fermented foods the presence of cadaverine, putrescine and tyramine, are undesired and can be used as indication for microbial spoilage. On the other hand, in fermented foods, several lactic acid microorganisms involved in the fermentation process, particularly enterococci could produce biogenic amines. Although BA could have an active role at the neurological level as neurotransmitters, their presence in food, particularly of histamine and tyramine are recognised as potential hazards causing intoxication and intolerance symptoms in healthy people. Furthermore, BA are potential precursors for the formation of carcinogenic nitrosamines. This review will focus on some food products and the relationship between the presence of BA according to their origin, inducing factors and distinctive characteristics of the technological processes that could control BA production in: I) animal foods, such as meat and meat products, including dry-fermented sausages, fish and seafood products and dairy products, such as cheeses; II) plant foods, like vegetables, with emphasis on table olives; III) beverages, such as wines, beers and liqueurs.